Effects of COVID-19 Lockdown on Physical Performance, Sleep Quality, and Health-Related Quality of Life in Professional Youth Soccer Players - Keemss, Jil; Sieland, Johanna; Pfab, Florian; Banzer, Winfried (Frontiers in Sports and Active Living, 2022)
Background: In March 2020, the COVID-19 outbreak led to the declaration of a pandemic. The accompanying restrictions on public life caused a change in the training routines of athletes worldwide. The present study aimed to investigate the effects of a 13-week supervised home training program on physical performance, sleep quality, and health-related quality of life in professional youth soccer players during the first COVID-19 lockdown in Germany. Methods: Eight professional soccer players (age range 16-19; height: 1.81 ± 0.07 m; body weight: 72.05 ± 6.96 kg) from a Bundesliga team in Germany participated in this study. During the lockdown, they trained 5 to 6 days per week with home-based training plans and were monitored via tracking apps and video training. To determine the effects of home training, measurements were taken before (March 2020) and after (June 2020) the home training period. Bioelectrical impedance analysis was used to determine body composition, and an isokinetic strength test and a treadmill step test, including lactate measurements, were used to measure physical performance. Two questionnaires were responded to in order to assess health-related quality of life and sleep quality. Results: When comparing measurements before and after the home training period, we observed significant increases in the following variables: body weight (72.05 ± 6.96 kg vs. 73.50 ± 6.68 kg, p = 0.034) , fat mass (11.99 ± 3.13 % vs. 13.98 ± 3.92 %, p= 0.030), body mass index (22.04 ± 0.85 kg/m2 vs. 22.49 ± 0.92 kg/m2, p= 0.049), and mental health component summary score (MCS) of the questionnaire SF-36 (53.95 ± 3.47 vs. 58.33 ± 4.50, p = 0.044). Scores on the general health (77.88 ± 14.56 vs. 89.75 ± 13.76, p= 0.025) and mental health (81.50 ± 9.30 vs. 90.00 ± 11.71, p= 0.018) subscales of the SF-36 also increased significantly. Conclusion: The COVID-19 lockdown led to an increase in body composition parameters and showed an improvement in the MCS of the SF-36. Physical performance and sleep quality could be maintained during the home training period. These observations may help trainers for future training planning during longer interruptions in soccer training.